A Mid-Turbinate Swab Appears Comparable to Nasopharyngeal Swabs for Quantitative Detection of RSV in Infants. (4th October 2017) - Blaschke, Anne J; Mckevitt, Matthew; Ampofo, Krow; Lewis, Tammi; Chai, Hao; Guo, Ying; Dorsch, Julianna; Vanderhoof, Erin; Rosen, Pricilla; Freimann, Volker; Korgenski, E Kent; Toback, Seth; et al.
Abstract: Background: Respiratory Syncytial Virus (RSV) is the most common cause of bronchiolitis and pneumonia in infants and children. Diagnosis of RSV can be made by molecular detection of the virus in a swab of respiratory secretions. Nasopharyngeal (NP) swabs are the most frequent swab type validated for the detection of RSV, and are often considered the "gold standard" for quantification studies. However, NP sampling is invasive and uncomfortable. We sought to determine whether a less invasive method, a mid-turbinate (MT) swab, was comparable to NP sampling for quantification of RSV in infants. Methods: We prospectively enrolled children < 24 months with a confirmed diagnosis of RSV and hospitalized at Primary Children's Hospital (Salt Lake City, UT) during the 2015 – 2017 RSV seasons. Both an NP and MT swab were collected from each infant from different nostrils; subjects were randomized (1:1:1:1) as to the order of collection. After collection, parents were asked which collection method (NP vs. MT) they preferred. Viral loads were measured by real-time RT-qPCR. Correlation between the viral loads from the MT and NP swabs was examined. A mixed effect model was used to evaluate the mean (SD) viral loads. Results: 83 infants were enrolled and had swabs collected. Median age was 4 months [range 0–23]. 20 infants had swabs collected on multiple consecutive days. Median (Q1, Q3) duration of symptoms prior to enrollment was 5 days (4, 7) Median (Q1, Q3) hospital stay length was 2 days (2, 4). 1 infant was RSV negative according to the RT-qPCR assay. The mean (SD) viral loads were similar: 7.34 (1.26) and 7.09 (1.25) log10 copies/mL for 77 paired NP and MT swabs, respectively; see Figure 1 for median, range and quartiles. The correlation coefficient between the paired viral loads was high (0.82); see Figure 2 for Bland-Altman plot. Most parents (49/67 [73%]) who watched the swabbing preferred the MT to the NP swab. Conclusion: MT swabs perform as well as NP swabs for the quantification of RSV in infants. The difference in mean viral load is small compared with the standard deviation. The less invasive MT swabs are preferred by parents for sampling. MT swabs have the potential to replace the NP swab as the "gold standard" for quantitative respiratory viral sampling. Disclosures: A. J. Blaschke, Gilead Sciences, Inc: Investigator, Research support BioFire Diagnostics, LLC: Collaborator, I have intellectual property in BioFire Diagnostics through the University of Utah and Investigator, Licensing agreement or royalty and Research support